"Sensory in-Service": An Exploratory Evaluation of a Group-Based, Caregiver Intervention for Children with Sensory Processing Difficulties. (4th March 2023) - Heyburn, Keith; Shaw, Deb; Carbert, Kayla; Thompson-Hodgetts, Sandy
Abstract: Aims: To describe and evaluate the effectiveness of a group-based, caregiver education intervention on: (1) functional concerns for children with identified sensory processing difficulties, (2) caregiver knowledge of sensory processing and strategies to support their child, and (3) resources required. Methods: Ninety-five caregivers of children referred to therapy because of sensory processing difficulties [72% male, mean age (SD) = 6.0 (2.3) years] participated in a structured, two-hour, group-based, caregiver education intervention, which included didactic information, group discussion, worksheets, and written resources. Canadian Occupational Performance Measure (COPM) performance and satisfaction scores evaluated changes in child function. A Caregiver Knowledge Questionnaire evaluated changes in caregivers' knowledge of sensory processing and strategies. Resources required were based on the total number of hours required for 1:1 versus group-based intervention. Results: Statistically significant and clinically meaningful improvements were found for COPM performance (W = 108, p < .001; EF = 0.95) and satisfaction scores (W = 119.5, p < .001; EF = 0.94) and caregiver knowledge (W = 0.00, p<.001; EF = 1.00). Group-based intervention used 62% less time than 1:1 intervention. Conclusions: Group-based, caregiver education can be an effective way for therapists to meet demand and improve caregiver self-efficacy related to sensory processing difficulties.